Pengembangan Sistem Informasi Pengelolaan Produksi Dan Penjualan UMKM Berbasis Web (Studi Kasus Rabbani Food) - Reza Ararsy Arrohman; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Rabbani Food is one of the MSMEs engaged in the processing of various types of souvenirs such as spinach chips, curry chips, vegetable sticks, etc. So far, these MSMEs are still carrying out production and operational activities in the form of home-based businesses where the MSMEs are still carrying out financial management using the manual method. This turns out to still cause a variety of problems such as the frequent occurrence of discrepancies in recording production and operational activities so that what is targeted is not achieved, for example such companies often do not know the supply of their products in the shops where the products are distributed. Then the management of bookkeeping records is still often unsuitable because each book of sales and production does not match the target produced where the information needed is often incomplete in the bookkeeping. From this problem, the author will create an information system that can manage the production, operations, and marketing of MSMEs so that the problem of incompatibility of data in the MSME business process can be minimized and can facilitate the company to manage its production and distribution activities. Work on information systems developed using the waterfall method. Testing in this study uses the type of Validation Testing and User Acceptance Testing. From the results of value 87.63% of acceptance testing witch it means it could be said that the system was well received by the user.